Mães de crianças autistas: sobrecarga do cuidador e representações sociais sobre o autismo - Dias, Camila Cristina Vasconcelos (2017)
Autism is considered a potential stressor stimulus for the family considering to what extent it undermines it. Generally, the mother assumes the role of the child's primary caregiver and may become vulnerable to the physical and emotional overload from the high investment in the routine tasks of direct maternal care. The present work aimed to know and analyze the social representations that mothers of autistic children have considering their overload. The theoretical base used for this work is the Social Representations Theory, for it recognizes the value of the subjective dimension and the cognitive aspect of the individual, which interfere in the social practices, attitudes and behavior referring to the object of the representation. This is a descriptive study, with a mixed approach, carried out in a public institution for the treatment of ASD in João Pessoa-PB, consisting of a sample of thirty mothers of autistic children. The instruments used were sociodemographic questionnaire, analyzed through the calculation of simple frequencies; The Free Speech Association and semi-structured interview, analyzed with IRAMUTEQ; and Zarit Burden Interview (ZBI), analyzed through descriptive and inferential statistics with SPSS. The results of the ZBI indicated the presence of moderate overload in the general sample, with a mean score of 38.53 (SD = 12.50), and from this data it was possible to establish two levels of overload to compare SRs performed by the mothers. Level one refers to a lower overload and level two to a higher overload. We observed that mothers who presented level one of overload, despite representing autism through negative contents, highlighting the difficulties, were more hopeful. On the other hand, mothers who presented level two of overload represented autism without affective content or hope, expressing caretaking as an obligation that reflects a challenge. In general, mothers represent autism as something difficult to deal with, signifying it in the difficulty of the exercise of caretaking, which demands patience and dedication. Daily care requires high investment from mothers who perform it solitary and full-time. In addition, participants considered autism as a mystery, which may be related both to the lack of definition of its etiology and consequently to the prognosis of the child, as well as to doubts about how to care for the child. Regarding the results found, we verified that the RS of autism changes considering the level of overload presented by participants, with the highest overload being related to an RS of autism of more negative contents. It is possible to identify that mothers objectify autism in their daily experiences with the child, which reflects their own overload, although they anchor it in love, indicating that they find in affection a source of motivation and overcoming adversity. With this research, we hope to provide scientific data that can contribute to the design of public policies aimed at improving the social support offered to these mothers, with strategies to support and prevent health complications both physical and emotional that arise from their overload. We believe that the data from this study may aid in awareness-raising programs about ASD, since negative social representations presented by mothers reflect what is in society and feed the caregiver's overload. We also hope to encourage reflection on the development of strategies aimed at reducing the negative contents of SR of autism elaborated by mothers, considering that SRs orient behavior and justify the attitudes of these mothers towards their autistic children, with such behavior directly related to children's development.